Mutu penggunaan dan tingkat kecukupan obat di 10 puskesmas kota Ambon=Quality of Drugs Use and Drugs Availability Level in Ten Health Service Centers of Ambon - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2002)
ABSTRACT Inappropriate use of drugs is a problem experienced by developing countries that results in big problem of decreasing quality of health service and increasing government's state budget allocated for drugs. This study was aimed to find out the quality and level of drugs availability in 10 health service centers in Ambon. This study was non experimental/observational, quantitative and qualitative method was used, cross-sectional design, data were analyzed descriptively. Prescription data were collected retrospectively from January 1 to 31 December 1998. The data gathered from daily patient registration records, prescription sheets, and patient status, which included prescription data of 3 diagnosis, i.e. non-pneumonia acute respiratory infection among under-five-year-old children and adults, non-specific acute diarrhea among under-five-year-old children and adults, and myalgia. There were 2349 cases. The drugs availability level in the pharmacy and health service centers was found out by observing the documents of drugs availability in the pharmacy and drugs prescription unit in the health service centers. Depth interviews were conducted with the pharmacy head, 2 head doctors of the health service centers, and 1 nurse who was the head of a health service center. The result showed that in average the number of drugs that a patient received were 3,8 - 5,1 items